PROSPEK IKAN NILA TERHADAP PENDAPATAN PETANI DI DESA SIGERONGAN LOMBOK BARAT - YUDI HERMAWAN (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine the total costs and income of farmers in Sigerongan Village, determine the contribution of tilapia to the income of farmers in Sigerongan Village, and find out the obstacles faced by farmers in tilapia business in Sigerongan Village. The research was conducted in Sigerongan Village, Lingsar District, West Lombok Regency. Determination of the research area is done by purposive sampling. A total of 25 tilapia farmers in Sigerongan Village were used as respondents in this study, with the data collection methods used were questionnaires and interviews. The variables measured in this study were the total income of farmers, the contribution of tilapia to farmers' income and the constraints faced by farmers in the tilapia business. In accordance with the first objective, an analysis of operating income is carried out, starting from total revenue, total operating costs and total net income. For the second purpose, a contribution analysis was carried out. The results showed: First, the total costs incurred for the tilapia fish business were Rp. 574,139,680,- while the net income is Rp. 728,700,320,-/year. Second, the contribution of freshwater fisheries to the total income of farmers in Sigerongan Village is Rp.728,700,320,-/year or 78% of the total income of farmers of Rp.894,023,262,-. Third, the problems faced in the tilapia business in Sigerongan Village, the first is the problem of capital. The high price of fish feed is one of the causes of the lack of capital. Second, the capacity of fish entrepreneurs and surrounding communities is still low in processing fishery products so that when fish products are abundant, the selling price will be relatively low